Evaluation of loneliness and its associated factors in caregivers of patients with dementia: a cross-sectional study (Colombia Medica, 2024)
Objective:To identify the levels of loneliness and the factors associated with the prevalence of loneliness in caregivers of patients with dementia.Methods: An observational cross-sectional study was conducted, including unpaid caregivers of patients with dementia who were receiving home care in Bogotá, Colombia. The prevalence of loneliness was estimated using the UCLA Loneliness Scale. Participants were also assessed regarding their satisfaction with providing care and whether they felt they received the necessary emotional support from family and friends. The association between loneliness and the patient's clinical variables, as well as the sociodemographic characteristics of the caregiver, was evaluated by calculating the odds ratio (OR) between the groups.Results:A total of 52 caregivers of patients with dementia were included. Severe loneliness was present in 5.77% of caregivers, while 26.92% experienced moderate loneliness. All caregivers reported feeling satisfied with providing care to their relatives, and 71% felt that their family or friends provided the emotional support they required. Loneliness was more common among caregivers of patients with total functional dependence (OR 4.061, P = 0.0278). Conversely, the perception of receiving emotional support from family and friends was identified as a potential protective factor against loneliness (OR 0.184, P = 0.0104).Conclusions: The prevalence of loneliness in this study is lower than that reported in previous studies. All caregivers reported satisfaction in providing care; most perceived adequate emotional support from family and friends. These factors could be contributing to the lower prevalence of loneliness observed.